ESTRATEGIAS DE APRENDIZAJES PARA DESARROLLAR EL LENGUAJE ORAL EN LOS NIÑOS DE INICIAL II - DIAZ MORENO LUISA HAYDEE (2024)
The research focuses on learning strategies to develop oral language in preschool II children. Oral language is important for cognitive, social and emotional development, its mastery is transcendental for your academic future. The objective is to establish learning strategies for the development of oral language in Level II children at the Mis Días Felices Early Education Center. It presents a descriptive methodology, with a quantitative approach of non-experimental design, we worked with 46 students and 2 teachers, the survey technique was used with 12 questions on a Likert scale and the observation sheet. 100% of teachers use learning strategies to improve oral language, 50% use role plays, story dramatizations, or work to promote oral language, 100% of children have difficulties in language development, They have a low level of reading fluency and do not articulate phonemes correctly; 100% of teachers involve parents in their children's school activities; sometimes teachers encourage verbal interaction with group activities. Conclusion, it is essential to address oral language difficulties from the beginning; The implementation of learning strategies effectively promotes oral language in students of the “Mis Días Felices” Education Center. Strategies based on linguistic and interaction experiences provide correct verbal communication and oral expression, thus promoting an environment of trust. . and emotional stability in children.